TRANSMISSION SPECTROSCOPY OF THE HOT JUPITER WASP-12b FROM 0.7 TO 5 μm - Stevenson, Kevin B.; Bean, Jacob L.; Seifahrt, Andreas; Désert, Jean-Michel; Madhusudhan, Nikku; Bergmann, Marcel; Kreidberg, Laura; Homeier, Derek (The Astronomical journal, 2014)
Since the first report of a potentially non-solar carbon-to-oxygen ratio (C/O) in its dayside atmosphere, the highly irradiated exoplanet WASP-12b has been under intense scrutiny and the subject of many follow-up observations. Additionally, the recent discovery of stellar binary companions~1" fromWASP-12 has obfuscated interpretation of the observational data. Here we present new ground-based multi-object transmission-spectroscopy observations of WASP-12b that we acquired over two consecutive nights in the red optical with Gemini-N/GMOS. After correcting for the influence of WASP-12's stellar companions, we find that these data rule out a cloud-free H2 atmosphere with no additional opacity sources. We detect features in the transmission spectrum that may be attributed to metal oxides (such as TiO and VO) for an O-rich atmosphere or to metal hydrides (such as TiH) for a C-rich atmosphere. We also reanalyzed NIR transit-spectroscopy observations of WASP-12b from HST/WFC3 and broadband transit photometry from Warm Spitzer. We attribute the broad spectral features in theWFC3 data to either H sub(2)O or CH sub(4) and HCN for an O-rich or C-rich atmosphere, respectively. The Spitzer data suggest shallower transit depths than the models predict at infrared wavelengths, albeit at low statistical significance. A multi-instrument, broad-wavelength analysis ofWASP-12b suggests that the transmission spectrum is well approximated by a simple Rayleigh scattering model with a planet terminator temperature of 1870 + or - 130 K. We conclude that additional high-precision data and isolated spectroscopic measurements of the companion stars are required to place definitive constraints on the composition of WASP-12b's atmosphere.